De-centring cultural studies : past, present and future of popular culture - Prieto Arranz, José Igor; Bastida Rodríguez, Patricia; Calafat-Ripoll, Caterina; Fernández Morales, Marta; Suárez Gómez, Cristina (Cambridge Scholars Publishing, 2013)
"The academic resistance that cultural studies has encountered remains especially visible in Eastern and Southern European countries. One such example is Spain, where cultural studies is seen at best as an emergent research field. Hence the interest of this volume, conceived in Spain by an all-Spanish editorial team and written by a diverse range of authors who prove that, in spite of all difficulties, cultural studies continues to bloom -- even in Southern and Eastern Europe. The different chapters offer interdisciplinary insights into a wide selection of cultural materials whose relevance goes well beyond purely aesthetic issues. Altogether, the volume (1) provides interesting theoretical reflections on the subtle (yet arbitrary) borders between popular and canonical culture; (2) explores how the popular culture of yesteryear has influenced and inspired later 'canonical' cultural materials; and (3) studies how the reception of, and representation in, popular culture can be accounted for from the crucially relevant perspectives of gender and age. This collection of essays studies and explores the connections between a wide range of materials, including relevant examples of classic and contemporary literature, Arthuriana, pop music and videos, political and mainstream film, newspaper advertising, television, and the phenomenon of the (trans)media star"--Provided by publisher